Uji Teratogenik Ekstrak Minyak Biji Jintan Hitam (Nigella sativa) pada Mencit (Mus musculus l.) Bunting - SETYAWATI, IRIANI; SUDATRI, NI WAYAN (Jurusan Biologi FMIPA Universitas Riau, 2016)
This experiment was performed to examine the effects of black cumin (Nigella sativa) seed oil extract onreproduction performance and fetus development if given during organogenesis period. Forty pregnantmice were randomly divided into four groups. Extract was treated orally by gavage with doses 0%(control), 0.1 ml, 0.2 ml, and 0.3 ml since gestation day 6 to 15. Caesarean section were performed topregnant mice on day 18 to remove fetuses. Observation covered reproduction performance i.e. the foetusnumber (reabsorptions, dead/ alive foetus), and morphological of the foetus (weight and length of thelitter, and malformations). Statistical analysis was performed using Anova and Duncans Multiple RangeTest. Teratogenic effects of black cumin oil extract caused decreasing of reproductive performance of themother (alive foetus decreased, dead and resorbed foetus increased) and an increased incidence of birthdefects (fetal weight and length and fetal hemorrhage).Keywords: Nigella sativa, congenital malformations